The synthesis of pyrimidine ketoamide molecules as EGFR inhibitors for cancer treatment. - Mathenjwa, Gcine Sindisiwe (My University, 2018)
The epidermal growth factor receptor (EGFR) is a major tyrosine kinase that is responsible for cell growth, differentiation and proliferation in human bodies. EGFR overexpression has been detected in various cancer cell lines. Hence, EGFR has been validated as a potential target for anti-cancer treatment. Monoclonal antibodies (MAbs) and tyrosine kinase inhibitors (TKIs) have been developed for EGFR inhibition. EGFR-TKIs have been found to be the most promising inhibitors, and hence there have been major research efforts towards their development. Gefitinib and erlotinib are first generation reversible EGFR-TKIs, but their main drawback is the development of drug resistance due to the T790M mutation. Afatinib is a second generation covalent irreversible EGFR-TKI that is active against the T790M mutant, however, it has a narrow therapeutic window that introduces severe side effects. Recently, covalent reversible EGFR-TKIs have been developed using various strategies: the use of the cyanoacrylate group as the active warhead is one strategy that is currently under development. In this project we aimed to synthesise anilino-pyrimidine ketoamides and ketoesters as a novel series of covalent reversible EGFR-TKIs. In the first part of this project eight anilinopyrimidine ketoamides were synthesised. Starting from 4,6-dichloropyrimidine a nucleophilic displacement of one chloro group was performed using monoprotected diethylene glycol yielding 4-chloro-6-{2-[2-(tetrahydro-2H-pyran-2-yloxy)ethoxy]ethoxy}pyrimidine. As a key step, an acid catalysed amination reaction was used to couple the functionalised pyrimidine with eight different aniline substrates. Using 3-bromoaniline as an example, this reaction yielded 2-{2-[4-(3-bromophenylamino)pyrimidin-6-yloxy]ethoxy}ethanol as an intermediate. After successful synthesis of the key intermediate, the hydroxy group was oxidised using 2iodoxybenzoic acid (IBX) to afford 2-{2-[4-(3-bromophenylamino)pyrimidin-6yloxy]ethoxy}acetaldehyde. The Passerini reaction was then used to convert the aldehyde to an α-hydroxy amide functionality, thereby forming 2-hydroxy-N-isopropyl-3-{2-[4-(3bromophenylamino)pyrimidin-6-yloxy]ethoxy}propanamide. Finally, the α-hydroxy amide system was oxidised using IBX to afford the desired α-ketoamide system, thereby completing the synthesis of 2-hydroxy-N-isopropyl-3-{2-[4-(3-bromophenylamino)pyrimidin-6yloxy]ethoxy}propanamide and seven analogues. In the second part of this project, a similar synthetic approach was utilised in an attempt to synthesise anilino-pyrimidine ketoesters. Starting from 2-{2-[4-(3bromophenylamino)pyrimidin-6-yloxy]ethoxy}acetaldehyde; potassium cyanide was used to prepare 2-hydroxy-3-{2-[4-(3-bromophenylamino)pyrimidin-6-yloxy]ethoxy}propanenitrile. Functional group conversion from the cyanohydrin to α-hydroxy ester was attempted using methanol in an acidic medium but, unfortunately, an unexpected product was obtained. Instead of affording an α-hydroxy ester system, from this reaction we isolated an acetal of the original aldehyde. Unfortunately, the unsuccessful attempt to synthesise methyl-3-{2-[4(3-bromophenylamino)pyrimidin-6-yloxy]ethoxy}-2-hydroxypropanoate prevented further progress towards the synthesis of the targeted methyl-3-{2-[4-(3bromophenylamino)pyrimidin-6-yloxy]ethoxy}-2-oxopropanoate. A selection of the anilino-pyrimidine analogues were screened for anticancer activity in an in vitro MTT assay using five different cell lines. From the preliminary results, 2-{2-[4-(3-chloro4-fluorophenylamino)pyrimidin-6-yloxy]ethoxy}acetaldehyde was the only active compound with an IC50 = 48.74 μM against the MCF7 breast cancer cell line and an IC50 = 30.75 μM against the SF268 glioblastoma cell line.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Science, February 2018
Keywords: Epidermal Growth Factor Receptor; Pyrimidines--Metabolism; Protein kinases--Inhibitors--Therapeutic use; Drug targeting; ErbB Receptors; Neoplasms (Cancer)